Urban green space and urban biodiversity: Kuala Lumpur, Malaysia - Karuppannan, Sadasivam; Hj. Baharuddin, Zainul Mukrim; Sivam, Alpana; Daniels, Chris B. (Canadian Center of Science and Education, 2014)
Urban green space plays an important role in enhancing the quality of environment especially for urban biodiversity. Declining biodiversity around the world has received much attention among academics, professionals and citizens. The United Nations has declared year 2010 as the ‘International Year of Biodiversity’. Urban biodiversity movement is important to ensure healthy city environments. Despite this ongoing movement, urban dwellers have little knowledge about conservation of biodiversity particularly wildlife. Moreover, biodiversity has received little attention from built environment practices (Brown & Grant, 2005; Niemelä, 1999). In general, urban wildlife habitat is protected as reserved forest. Many species of wildlife are generally found in such reserved forests. In comparison, the scale of urban parks in Kuala Lumpur is massive, much larger than protected forests. This paper presents the situation of urban wildlife species and the quality of habitats in Kuala Lumpur. It is found that many factors contribute to the healthy conservation of urban wildlife such as quality and variety of habitats, ornamental versus native vegetation and ecological design. The findings highlight that common urban birds are dominant in urban green spaces regardless of the size of the green spaces. However, only larger urban green spaces help protect species. Finally, the study concludes that urban wildlife in Kuala Lumpur is rapidly declining and that there is a greater need for the community and stakeholders to promote programs and activities to preserve and enhance urban wildlife. Development of comprehensive acts, policies and guidelines are vital for urban wildlife protection.